Dynamic Depositor Discipline: Evidence Based on East Asian Banks. (August 2015) - Hamid, Fazelina Sahul
This study confirms the endogenous relationship between the price and quantity of deposits in the depositor discipline model. Dynamic panel data analysis is carried out to account for the lagged dependency of the deposits growth variable and endogeneity of the price mechanism in the depositor discipline model. The results show that depositors in East Asia do not demand a higher price for deposits. Analysis by subdividing the sample of banks into healthy and weak banks shows that the relationship between price and quantity is not non-linear. Healthy banks are not able to attract more deposits by raising price. Depositors do not discipline weak banks by demanding a higher return. Lack of responsiveness by depositors to price signals may be attributable largely to the outflow of deposits that happened during the crisis period and regulations on interest rates. JEL Classification: G21, G28, N25